2001
DOI: 10.1002/1521-379x(200109)53:9<431::aid-star431>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Extent of Conversion and Retrogradation on the Digestibility of Potato Starch

Abstract: Finally, the effect of the retrogradation of the amylopectin fraction on its digestibility was assessed in extruded potato starch ribbons containing 35% (w/w) water and stored at different temperatures. After 14 days of storage, the digestibility decreased from 77.0 ± 0.9% in the freshly extruded samples to between 28.0 ± 1.7% and 42.1 ± 0.3%, depending on the storage temperature. This suggested a measurable difference in the α-amylase susceptibility between the A and B polymorphs of retrograded amylopectin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 17 publications
0
25
0
Order By: Relevance
“…It can be observed from Table 2 that the final (30 days) retrogradation enthalpy of S68 is very close to that of S70 even though S68 contains more ordered structure. It can also be observed from Table 2 that the final retrogradation enthalpy of S70 is four times as high as that of S64, which means that the degree of gelatinization has a significant impact on the retrogradation rate of starch (Farhat et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…It can be observed from Table 2 that the final (30 days) retrogradation enthalpy of S68 is very close to that of S70 even though S68 contains more ordered structure. It can also be observed from Table 2 that the final retrogradation enthalpy of S70 is four times as high as that of S64, which means that the degree of gelatinization has a significant impact on the retrogradation rate of starch (Farhat et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…From the four RS types, RS3 seems to be particularly interesting because it retains its indigestibility when added as an ingredient to processed foods. RS3 is produced by a combination of the gelatinization process, which is a disruption of the granular structure by heating starch with an excess of water (Farhat et al, 2001); and retrogradation, a slow recrystalization of starch components (amylose and amylopectin) upon cooling or dehydration (Shamai et al, 2003). As it was mentioned before, modern food manufacturing methods destroy most forms of resistant starch, making them unsuitable as ingredients in highly processed food systems.…”
Section: Introductionmentioning
confidence: 99%
“…Fabbri et al [13] and Perdon, et al [14] reported that cooling process will stimulate the formation of RS 3. The formation of RS 3 due to retrogradation process were reported also by Vasanthan and Bhatty [7]; Fredriksson et al [15]; Farhat et al [16]; Thompson [17]; Fuentes-Zaragoza et al [18]. (Table 1).…”
Section: Resistant Starch Contentmentioning
confidence: 99%